Pemodelan Matematis Hubungan Kadar Air Tepung dengan Variabel Proses pada Pengeringan Mekanis Tepung Kasava Menggunakan Pneumatic Dryer - Yus Witdarko; Nursigit Bintoro; Bandul Suratmo; Budi Rahardjo (agriTECH, 2016)
Moisture content of the materials (Ka) is the most important variable in evaluating the performance of drying process, therefore the ability to predict moisture-content of the materials in the drying process is very important. The objective of this research was to formulate a mathematical relationship between various pneumatic drying process variables and the moisturecontent of the materials of cassava flour by applying dimensional analysis. In this research, a pneumatic drying equipment and test edit in wide varieties of treatments, such as the input capacity, drying air temperature, and drying air velocity. Based on the result of data analysis, it was obtained that the relationship between moisture content of the materials and the drying process variables could be expressed as followThis equation had 0,722 coefficient of determination, so that it could be used to predict the moisture content of cassava flour precisely. Sensitivity analysis indicated that the dimensionless product which had the largest effect on Ka was.ABSTRAKKadar air bahan (Ka) merupakan variabel yang paling penting dalam mengevaluasi kinerja proses pengeringan bahan, sehingga kemampuan untuk memprediksi Ka dalam proses pengeringan akan menjadi sangat penting. Penelitian ini bertujuan untuk memformulasikan hubungan matematis antara berbagai variabel proses pengeringan secara pneumatik dengan Ka akhir tepung ketela pohon dengan menerapkan analisis dimensi. Pada penelitian ini telah dirancang peralatan pneumatic drying dan dilakukan pengujian dengan berbagai macam variasi perlakuan seperti kapasitas input, temperatur udara pengering, dan kecepatan udara pengering. Berdasarkan hasil analisis data maka diperoleh hubungan antara Ka dengan variabel-variabel proses pengeringan sebagai berikut:Persamaan tersebut mempunyai nilai koefisien determinasi 0,722 sehingga besar kemungkinan untuk dapat digunakan sebagai alternatif dalam memprediksi kadar air tepung hasil pengeringan. Hasil uji sensitivitas menunjukkan bahwa dimensionless product yang paling berpengaruh terhadap nilai Ka adalah    ்ೠ   .